HAKEKAT HUKUM PENGUPAHAN DALAM UPAYA MEWUJUDKAN KESEJAHTERAAN SOSIAL PEKERJA - H. Zulkarnain Ibrahim (Faculty of Law, Universitas Diponegoro, 2015)
The values of Pancasila are reflected in legal idea that showed in moral standards. The legal idea is a pattern of thought that contains sublime rules, leads the remuneration law’s direction and goal to create a prosperous life for society workers. The essence of Pancasila, law of idea, and moral become benchmark for government, enterpreneurs, and workers to execute the harmonious of Pancasila’s Industrial Relationship system in legal certainty, justice, and expedienceNilai-nilai Pancasila, tercermin pada cita hukum yang nampak pada standar moral. Cita hukum tersebut merupakan suatu pola pikir yang mengandung kaedah-kaedah luhur menentukan arah dan tujuan hukum pengupahan dalam rangka mewujudkan masyarakat pekerja yang hidup sejahtera. Hakekat Pancasila, cita hukum, dan moral tersebut, menjadi tolak ukur dari pemerintah, pengusaha dan pekerja dalam melaksanakan sistem Hubungan Industrial Pancasila (HIP) yang harmonis dalam kepastian hukum, keadilan dan kehasilgunaan